Pengaruh Biaya Audit, Kantor Akuntan Publik, dan Komite Audit Terhadap Hal Audit Utama - Audrey Alvania; Christina Dwi Astuti (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
This study aims to analyze the influence of audit fees, audit firms, and audit committees on Key Audit Matters. A quantitative approach was employed using secondary data obtained from annual reports and independent auditor reports. The study population includes companies in the cyclical and non-cyclical sectors listed on the Indonesia Stock Exchange (IDX) during the 2022–2023 period. The purposive sampling method was used to select the sample, resulting in 202 samples that met the research criteria. The data were analyzed using a multiple regression model processed with SPSS software. The findings reveal that audit firms and audit committees have a positive influence on Key Audit Matters. However, audit fees do not show an impact on Key Audit Matters.